Clinical Performance of the Xpert® CT/NG Test for Detection of Chlamydia trachomatis and Neisseria gonorrhoeae: A Multicenter Evaluation in Chinese Urban Hospitals - Han, Yan; Shi, Mei-Qin; Jiang, Qing-Ping; Le, Wen-Jing; Qin, Xiao-Lin; Xiong, Han-Zhen; Zheng, He-Ping; Tenover, Fred C.; Tang, Yi-Wei; Yin, Yue-Ping (Frontiers in Cellular and Infection Microbiology, 2022)
Background: To evaluate the clinical performance of the Xpert® CT/NG assay for detection of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) using urine and cervical swabs collected from patients in China. Methods: This study was conducted from September 2016 to September 2018 in three Chinese urban hospitals. Results from the Xpert CT/NG (Xpert) test were compared to results from the Roche cobas 4800 CT/NG test; discordant results were confirmed by DNA sequence analysis. Results: In this study, 619 FVU specimens and 1,042 cervical swab specimens were included in the final data set. There were no statistical differences between the results of the two tests for detection of CT/NG in urine samples (p>0.05), while a statistical difference was found in cervical swabs (p<0.05). For CT detection, the sensitivity and specificity of Xpert test were 100.0% (95%CI: 96.8%-99.9%) and 98.3% (95%CI: 96.6%-99.2%) for urine samples, and 99.4% (95%CI: 96.5%-100.0%) and 98.6% (95%CI: 97.5%-99.2%) for cervical swabs, respectively. For NG detection, the sensitivity and specificity of the Xpert test were 99.2% (95%CI: 94.9%-100.0%) and 100.0% (95%CI: 99.0%-100.0%) for urine, and 100% (95%CI: 92.8%-100.0%) and 99.7% (95%CI: 99.0%-99.9%) for cervical swabs, respectively. Conclusion: The Xpert CT/NG test exhibited high sensitivity and specificity in detection CT and NG in both urine and cervical samples when compared to the reference results. The 90 minutes turnaround-time for CT and NG detection at the point of care using Xpert may enable patients to receive treatment promptly.